Clear aligners brands and marketing claims: An overview of available information on the web - Shi Cynthia; Feng Yanlu; Hsiao Yu-Chen; Smith Julia; Jin Carrol; Farella Mauro; Mei Li (Sciendo, 2022)
To investigate the current commercially available clear aligners related to brands, companies, Google trends, and marketing claims presented on their official websites.